Hippocampal neurogenesis protects against cocaine‐primed relapse. (24th December 2012) - Deschaux, Olivier; Vendruscolo, Leandro F.; Schlosburg, Joel E.; Diaz‐Aguilar, Luis; Yuan, Clara J.; Sobieraj, Jeffery C.; George, Olivier; Koob, George F.; Mandyam, Chitra D.
Abstract Accumulating evidence demonstrates a functional role for the hippocampus in mediating relapse to cocaine‐seeking behavior and extinction‐induced inhibition of cocaine seeking, and dentate gyrus neurogenesis in the hippocampus may have a role. Here, we tested the hypothesis that disruption of normal hippocampal activity during extinction alters relapse to cocaine‐seeking behavior as a function of dentate gyrus neurogenesis. Adult rats were trained to self‐administer cocaine on a fixed‐ratio schedule, followed by extinction and cocaine‐primed reinstatement testing. Some rats received low‐frequency stimulation (LFS; 2 Hz for 25 minutes) after each extinction session in the dorsal or ventral hippocampal formation. All rats received an injection of the mitotic marker 5‐bromo‐2′‐deoxyuridine (BrdU) to label developing dentate gyrus neurons during self‐administration, as well as before or after extinction and LFS. We found that LFS during extinction did not alter extinction behavior but enhanced cocaine‐primed reinstatement. Cocaine self‐administration reduced levels of 24‐day‐old BrdU cells and dentate gyrus neurogenesis, which was normalized by extinction. LFS during extinction prevented extinction‐induced normalization of dentate gyrus neurogenesis and potentiated cocaine‐induced reinstatement of drug seeking. LFS inhibition of extinction‐induced neurogenesis was not due to enhanced cell death, revealed by quantification of activated caspase3‐labeled cells. These data suggest that LFS during extinction disrupts hippocampal networking by disrupting neurogenesis and also strengthens relapse‐like behaviors. Thus, newly born dentate gyrus neurons during withdrawal and extinction learning facilitate hippocampal networking that mediates extinction‐induced inhibition of cocaine seeking and may play a key role in preventing relapse.